Decision Analysis to Find the Best Solution to Overcome Instrumentation Problems by Using Analytic Hierarchy Process and SMART Method - Hatian Ojak Somonggal; Santi Novani (Universitas Kristen Maranatha, 2022)
The Laksmana offshore area is one of the oil field areas under Sumatera field. Laksmana offshore area produces 750 BOPD (Barrel Oil per Day). Instrumentation plays a vital role in the production process since it controls the Fluid Flow, level, and pressure. Based on the data collected from January 7th, 2020, to December 6th, 2020, there were 13 unplanned shutdowns caused by instrumentation system failures. This instrumentation systems failure can be grouped into three major categories: Air compressor failure, Instrumentation valve problems, and Instrument equipment malfunctions. Researchers attempted to stratify the problem using a Pareto diagram and find the root cause using a fishbone diagram and Failure Mode Effect Analysis. From the stratifying process, it was found that the company does not yet have any methods and facilities to monitor the condition of the compressor in real-time, so it is difficult to analyze and know the early signs of air compressor failure. The researcher conducted value-focused thinking with three members in a focus group discussion and generated four alternative solutions that can be used. The first alternative is installing the HMI (Human Machine Interface/SCADA) system. The second alternative is to purchase and use the S551 Data Logger. The third alternative is the assembly of own innovation tools made by the Laksmana’s worker, and the last is to appoint extra personnel for daily monitoring of the compressor. This research uses the Analytic Hierarchy Process (AHP) and Simple Multi-Attribute Rating Technique (SMART) methods to determine the best alternative and found that the own innovation tool is the best alternative.